Empowering Grandmothers through Educational Media: A Quasi-Experimental Study on Stunting Prevention in Yogyakarta, Indonesia - Eka Oktavianto; Endar Timiyatun; Woro Ispandiyah (Caring: Indonesian Journal of Nursing Science, 2025)
Stunting remains a major public health issue in Indonesia, with multifactorial causes. Grandmothers play a central role in childcare and decision-making within families. Effective educational media are needed to improve knowledge and caregiving practices in family settings. This study aimed to examine the effectiveness of educational modules and videos in improving grandmothers’ knowledge and skills in providing health education for stunting prevention. A one-group pretest–posttest quasi-experimental design was conducted among 25 grandmothers who lived with or near their grandchildren. The educational media (module and video) were first validated by experts. The materials included comprehensive information on the definition, causes, signs, symptoms, impacts, and prevention of stunting, as well as methods and techniques for delivering effective health education. Data were collected using knowledge and skill assessment tools, and analyzed using the Wilcoxon signed-rank test due to non-normal data distribution. The results showed that mean knowledge score of grandmothers significantly increased from 69.6 (pretest) to 94.4 (posttest), with a mean difference of 24.8, Z-score = -4.391, p-value = 0.000 (p < 0.001). Similarly, the mean skill score in delivering health education improved from 50.20 (pretest) to 84.80 (posttest), with a mean difference of 34.6, Z-score = -4.298, p value = 0.000 (p < 0.001). Educational modules and videos are effective in improving grandmothers’ knowledge and skills in providing health education for stunting prevention. Integrating family-centered educational tools into community health programs may strengthen family support and contribute to reducing stunting prevalence. Keyword: Stunting, Grandmother, Health education, Educational module, Video